Are there any relationships between umbilical artery Pulsatility Index and macrosomia in fetuses of type I diabetic mothers?. (November 2014) - Maruotti, G. M.; Rizzo, G.; Sirico, A.; Sarno, L.; Cirigliano, L.; Arduini, D.; Martinelli, P.
Abstract Objective: To establish whether there are relationships between umbilical artery Pulsatility Index (PI) and fetal macrosomia in pregnancies complicated by type I diabetes. Methods: In a retrospective observational study, 102 singleton pregnant women with type I diabetes were considered. Umbilical artery PI was measured by Doppler ultrasonography within one week from delivery and related to neonatal weight. Pregnancies were grouped according to birtweight in macrosomic group (≥4000 g) and normal growth group (<4000 g). Relationships between umbilical artery PI and birth weight and birth weight centile were tested by Pearson's correlation analysis. Further umbilical artery PI values were compared between macrosomic and normally grown fetuses. Results: Birth weight was ≥4000 g in 24 pregnancies (23.5%). A significant relationship was found between umbilical artery PI and neonatal weight (r = 0.512; p < 0.01) and neonatal weight centile (r = 0.400; p < 0.01). Umbilical artery PI were significantly lower (t = −6.013; p < 0.001) in the macrosomic group (0.78; 95% confidence interval (CI) 0.73–0.84) than in the normal growth group (1.00; 95% CI 0.97–1.04). Conclusions: In pregnancies complicated by type I diabetes there is a significant relationship between umbilical artery PI value before delivery and absolute birth weight and birth weight centile. Macrosomic fetuses show a significant reduction in umbilical artery PI when compared with diabetic pregnancies without fetal overgrowth.